Trading system of food commodity - Harini, H.; Purwaningsih, Yunastiti; Widiyanti, Emi; Cahyadin, Malik (Economic Journal of Emerging Markets, 2017)
Most of food commodities in the Central Java are produced and traded in the local market. The aim of this research is to analyse internal and external factors determining trade of food commodities and analyse its trade model in Central Java. Research data consist of both primary and secondary that were analysed according to SWOT and Location Quotient (LQ) methods. The analysis of internal factors suggests that the availability and the quality of food commodities as well as the regulations related to traditional markets still need to be improved. The analysis of external factors proves that the local production is subject to be increased. Based on LQ results it shows that the agricultural sector in Central Java is highly specialised and has a strong base sector.